الخطاب الأنثروبولوجي في عالمه الإسلامي - واعر, آسيا (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
Anthropologyisa science dedicated to the study of the humanbeing In a holisticway. It is an inclusive science thatstudies man in the context of the society and culture to whichhebelongs, Whilecombiningapproaches to natural, social and human sciences. In otherwords, this science studies the origin and development of humanvariability and social behavior patterns across time and space, Has itsown original researcharobo-Islamicthought, thisiswhatwefoundwith the anthropologist "Akbar. S. Ahmed”.